(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of the study was to find out the effect of Hatha Yoga practice on psycho-physical fitness variables on women. For the purpose of the study 20 Women from Maharashtriya Mandal Gultekdi, Pune, Maharashtra were randomly selected as subjects for the study, The Single Group Experimental research design was framed for this study. The selected sample underwent one month of Hatha Yoga practice five days in a week for one-hour duration. Pretest and post-test were conducted on the selected psycho-physical fitness variables of women such as Anxiety, Depression, Stress, Flexibility, Body Mass Index. The mean, standard deviation and ‘t’ test were calculated, and the level of significance was set at 0.05. The results showed the significant mean difference in Anxiety level, Depression level, Stress level, Flexibility, and Fat level, of the subjects after 8 weeks of Hatha Yoga practice. In conclusion, it appeared that the Hatha Yoga practice program resulted in improvement of psycho-physical fitness in women.